Neural response after a single ECT session during retrieval of emotional self-referent words in depression: a randomized, sham-controlled fMRI study - Miskowiak, K; Macoveanu, J; Jørgensen, M; Støttrup, M; Ott, C; Jensen, H; Jørgensen, A; Harmer, C; Paulson, O; Kessing, L; Siebner, H (Oxford University Press, 2017)
Background Negative neurocognitive bias is a core feature of depression that is reversed by antidepressant drug treatment. However, it is unclear whether modulation of neurocognitive bias is a common mechanism of distinct biological treatments. This randomized controlled functional magnetic resonance imaging study explored the effects of a single electroconvulsive therapy session on self-referent emotional processing. Methods Twenty-nine patients with treatment-resistant major depressive disorder were randomized to one active or sham electroconvulsive therapy session at the beginning of their electroconvulsive therapy course in a double-blind, between-groups design. The following day, patients were given a self-referential emotional word categorization test and a free recall test. This was followed by an incidental word recognition task during whole-brain functional magnetic resonance imaging at 3T. Mood was assessed at baseline, on the functional magnetic resonance imaging day, and after 6 electroconvulsive therapy sessions. Data were complete and analyzed for 25 patients (electroconvulsive therapy: n = 14, sham: n = 11). The functional magnetic resonance imaging data were analyzed using the FMRIB Software Library randomize algorithm, and the Threshold-Free Cluster Enhancement method was used to identify significant clusters (corrected at P < .05). Results A single electroconvulsive therapy session had no effect on hippocampal activity during retrieval of emotional words. However, electroconvulsive therapy reduced the retrieval-specific neural response for positive words in the left frontopolar cortex. This effect occurred in the absence of differences between groups in behavioral performance or mood symptoms. Conclusions The observed effect of electroconvulsive therapy on prefrontal response may reflect early facilitation of memory for positive self-referent information, which could contribute to improvements in depressive symptoms including feelings of self-worth with repeated treatments.